Identification of patients at risk of cardiovascular disease in Greater Manchester in the VICTORION-Spirit study - Gibson, J. Martin; McCrae, John; Williams, Claire; Wilson, Paul M.; Bower, Peter; Dixon, Samantha (International Journal of Clinical Trials, 2024)
Background: Inclisiran is a cholesterol-lowering small interfering RNA treatment licensed in the UK for lowering low-density lipoprotein cholesterol (LDL-C). VICTORION-Spirit (NCT04807400) is an implementation science study designed to provide evidence for inclisiran implementation within the National Health Service. The aim was to describe the process of patient identification employed in VICTORION-Spirit. Methods: A Phase IIIb, multicentre, randomised controlled study, VICTORION-Spirit is evaluating inclisiran implementation in participants with atherosclerotic cardiovascular disease (ASCVD) or ASCVD-risk equivalents and elevated LDL-C. Feasibility Assessment and Recruitment System for Improving Trial Efficiency (FARSITE) software utilising natural language search functions identified patients who may benefit from inclisiran. FARSITE searches were performed within Salford, Manchester, Trafford and Bury Clinical Commissioning Groups to identify individuals with elevated LDL-C or total cholesterol and pre-existing cardiovascular disease (CVD) or at risk of ASCVD. Results: FARSITE used ‘total cholesterol >4 mmol/l’ terminology rather than ‘LDL-C’; the former yielded >3 times the number of eligible patients. The search for individuals with pre-existing CVD identified 24,196 people in a population of 560,969 (4.3%); including ‘total cholesterol >4 mmol/l’ identified 10,431 individuals with pre-existing CVD and elevated total cholesterol. Searches for individuals at risk of ASCVD identified 65,457 people, narrowing to 26,580 at risk of ASCVD plus elevated total cholesterol. The most discriminatory SNOMED concept codes and their prevalence within the dataset can inform national approaches to develop similar searches. Conclusions: FARSITE searches employed in VICTORION-Spirit identified a population at risk of ASCVD in Greater Manchester, England, who may benefit from a cholesterol-lowering medication such as inclisiran.